Symbolism and role of water in traditional Islamic Gardens - Abdul Latiff, Zainab; Mohd Yunus, Yazid; Mydin, Md Azree Othuman (INSInet Publication, 2016)
Water is an indispensable element of the Islamic Garden. It symbolizes life and mercy while its pleasant sight and sound give comfort and pleasure and thus make people feel grateful to Allah. Therefore, this study is conducted to apprehend and acknowledge the distinguished characteristics of water mentioned in the Holy Quran and Hadiths that describe Paradise. As to achieving the purpose of the study, the method of content analysis has been carried out with some cross reference to Ibn Kathir’s compilation of tafsir by Al Asgalani and the writings of Said Nursi. The study concludes that water in Paradise is referred to as ‘rivers’ that constantly flow. There are five types of water features in Paradise which are rivers, fountains, springs, wells and streams. The qanats are the earliest example of water technology by Muslims introduced by the Persians. The court of the Lions elaborates precisely the Qur’anic verse of "Gardens underneath which rivers flow”.